Mood self-assessment on smartphones - KHUE, Le Minh (Institutional Knowledge at Singapore Management University, 2015)
Mood has been systematically studied by psychologists for over 100 years. As mood is a subjective feeling, any study of mood must take into account and accurately capture user’s perception of an experienced feeling. In last 40 years, a number of pen-andpaper mood self-assessment scales have been proposed. Typically, a person is asked to separately rate various dimensions of the experienced feeling (e.g., pleasure and arousal) or mood items (interested, agitated, excited, etc.) on numeric scales (e.g., between 0 and 10). These partial ratings are then combined into an overall mood rating (or into its positive and negative affect). Penand-paper mood scales are used in basic research on mood and in clinical practice. Mobile technology makes it possible to extend mood self-assessment from lab to real life rather, collecting mood data frequently, over long time, in variety of life situations. With these motivations, we developed mobile versions of validated pen-and-paper scales for mood self-assessment to facilitate accurate in-situ mood self-assessment in real-life situations by smartphone users. The novelty of our Mobile Mood Scales (MMS) app is the use of visual effects such as color, changing brightness, animation and photos. We believe these mobiletechnology-enabled aids involving user’s senses can make mood self-assessment more intuitive and engaging for users than penand-paper mood scales that rely on linguistic terms and numerical rating. We built a customization layer that allows a doctor to generate a required mood app by selecting the mood scale required (e.g., PANAS or SPANE) as well as specific optional features such as the granularity of a rating scale (e.g., 5-point scale with radio buttons) and visual effects. In an evaluation survey, 61% of 48 participants found special features such as use of color, brightness and photos helpful in reflecting on own mood. 83% of 48 participants preferred mobile mood scales over penand-paper scales. We received encouraging feedback from the designers of original pen-and-paper mood scales. We envision applications of MMS in psychological studies of mood, in monitoring the efficacy of medical interventions and medication, as a component for mHealth apps where it is important to know fluctuations of patient’s mood. Permission to make digital or hard copies of all or part of this work for personal or classroom use is granted without fee provided that copies are not made or distributed for profit or commercial advantage and that copies bear this notice and the full citation on the first page. Copyrights for components of this work owned by others than ACM must be honored. Abstracting with credit is permitted. To copy otherwise, or republish, to post on servers or to redistribute to lists, requires prior specific permission and/or a fee.